Pengaruh Company Size, Profitabilitas, Leverage dan Capital Intensity Terhadap Tax Avoidance (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2016-2020) - Jenesia Jenesia (eCo-Buss, 2022)
The review means to inspect the effect of firm size, benefit, influence, and capital force on charge aversion. Charge aversion is estimated by utilizing the money compelling expense rate (CETR) of assembling organizations in the food and drinks sub-area recorded on the Indonesian stock trade from 2016-2020. The information utilized in this study is auxiliary information, the 2016-2020 monetary report downloaded from www.idx.co.id. The review populace utilized food and drink organizations recorded on the Indonesian stock trade from 2016-2020, up to 29 organizations. Utilize deliberate testing strategies to recognize tests that meet example determination measures. Qualified research tests, that is to say, up to 12 endeavor tests during the 5-year time frame. The scientific procedure utilized was direct relapse investigation and handled utilizing the SPSS program form 25. In light of the consequences of examination on free factors against charge evasion, iwas presumed that organization size got a critical worth of 0.011, productivity of 0.595, influence of 0.672 and capital power of 0.145. The main variable that influences are organization size against charge evasion. Nonetheless, the aftereffects of synchronous test, every free factor, to be specific organization size, benefit, influence and capital power have an impact against charge evasion with a huge worth of 0.019.